A software development : business plan and feasibility assessment - Daníel Auðunsson 1982- (2015)
This thesis examines how to build a perfect business plan and use the information to determine the presumptions for a feasibility assessment. When developing software it is important to confirm that there is a demand from the market. If there is a demand then the next question is if it is possible to gain profits. An overview of the innovation community in Iceland is presented, as well as a brief overview of a business plan buildup, which will be used as a guide for the case study along with feasibility methods. The case study illustrates the use of building a business plan and a feasibility assessment model for Verkvaki software development. The conclusion is that despite a need from the market and a promising cash flow, software development is an expensive process and in this case not feasible. Support from the innovation society in forms of grants or venture capitalists are essential and exportation should be considered from the beginning to gain more buyers. Þessi ritgerð skoðar hvernig byggja á hina fullkomnu viðskiptaáætlun og nota upplýsingarnar úr henni sem forsendur fyrir arðsemismat. Við hugbúnaðarþróun er mikilvægt að staðfesta að það sé þörf frá markaðnum. Ef þörfin er til staðar er hægt að skoða hvort hugmyndin sé arðbær. Yfirlit yfir frumkvöðlaumhverfið á Íslandi er kynnt auk yfirlits yfir hvernig byggja á viðskiptaáætlun sem notað verður sem leiðarvísir fyrir rannsóknardæmi þar sem gert verður að lokum arðsemismat. Dæmið mun sýna fram á hvernig byggð er viðskiptaáætlun og arðsemismat í kringum hugbúnaðinn Verkvaki. Niðurstöðurnar gefa til kynna að þrátt fyrir góða hugmynd og upprennandi fjármagnsstreymi þá er hugbúnaðarþróun dýr og í þessu tilfelli ekki arðbær. Stuðningur frá frumkvöðlaumhverfinu í formi styrks eða áhættufjárfesti er nauðsynlegur auk þess sem huga ætti að útlutningi strax frá fyrstu skrefum.